Thresholds of Listening : Sound, Technics, Space. - Maas, Sander van (Fordham University Press, 2015)
This collection of essays addresses recent and historical changes in the ways in which listening has been conceived as a cultural agency and act. It argues that listening, by emancipating from an essentially implied, passive-receiving, and subjected position, has become an explicit factor in culture and the object of proactive collective and individual politics.